Introduction of alkanet (Alkanna tinctoria (L.) Tausch), a traditional dye plant into cultivation - Pluhár, Zs.; Bernáth, J.; Hermándy-Berencz, J. (International Journal of Horticultural Science, 2001)
As a part of the research project to establish natural sources of plant pigments, possibilities of introduction of Alkanna tinctoria (alkanet) into cultivation were studied. As a result of the germination experiment, the relevance of 21 days’ duration of germination procedure was proved. To get high germination rate alkanet fruits are proposed to pretreat by gibberellinic acid (GA3) in the concentration of 400 ppm, overnight before sowing. This method results approximately 50 % germination rate. The morphological and production properties of alkanet roots are characterized during ontogenesis. Transplanted populations can be characterized by numerous, thick and heavy roots comparing to the spontaneous ones. Thus, seed sowing and transplantation proved to be an effective method for cultivation of the species. According to our results it can be concluded that in cultivation the optimal harvesting time of roots is at the end of the second vegetation cycle, when the dry root mass of the individuals is about 10-20 g with 3,0-3,5 % accumulation level of active substances. Considerable seasonal variability have been found influencing not only the root masses, but also the accumulation levels of alkannin derivatives. In a more humid vegetation cycle the root size and mass as well as the content of active substances are much higher.